Correlated Information and Mecanism Design - McAfee, R. Preston; Reny, Philip J. (Econometrica, 1992)
In models of asymmetric information, possession of private information leads to rents for the possessors. This induces mechanism designers to distort away from efficiency. The authors show that this is an artifact of the presumption that information is independently distributed. Rent extraction in a large class of mechanism design games is analyzed, and a necessary and sufficient condition for arbitrarily small rents to private information is provided. Additionally, the two-person bargaining game is shown to have an efficient solution under first-order stochastic dominance and a hazard rate condition. Similar conditions allow full rent extraction in Milgrom-Weber auctions.